2008
DOI: 10.1186/1471-2164-9-231
|View full text |Cite
|
Sign up to set email alerts
|

PPARalpha-mediated effects of dietary lipids on intestinal barrier gene expression

Abstract: BackgroundThe selective absorption of nutrients and other food constituents in the small intestine is mediated by a group of transport proteins and metabolic enzymes, often collectively called 'intestinal barrier proteins'. An important receptor that mediates the effects of dietary lipids on gene expression is the peroxisome proliferator-activated receptor alpha (PPARα), which is abundantly expressed in enterocytes. In this study we examined the effects of acute nutritional activation of PPARα on expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 108 publications
2
48
0
Order By: Relevance
“…Although no precise mechanisms have been established, there are possible explanations. First, the Niemann-Pick C1-like 1 (NPC1L1) gene is reported to be downregulated by the activation of PPARα by its agonists, such as WY14643, eicosapentaenoic acid and docosahexaenoic acid 25) . Since the PPARα gene expression is decreased 26) and the n-3 polyunsaturated fatty acid profile is unfavorably altered 27) in patients with renal failure, intestinal cholesterol absorption via NPC1L1 could be increased in subjects with a decreased renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Although no precise mechanisms have been established, there are possible explanations. First, the Niemann-Pick C1-like 1 (NPC1L1) gene is reported to be downregulated by the activation of PPARα by its agonists, such as WY14643, eicosapentaenoic acid and docosahexaenoic acid 25) . Since the PPARα gene expression is decreased 26) and the n-3 polyunsaturated fatty acid profile is unfavorably altered 27) in patients with renal failure, intestinal cholesterol absorption via NPC1L1 could be increased in subjects with a decreased renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that PPAR ␣ activation in intestinal epithelial cells reduces postprandial hyperlipidemia, it was unknown whether postprandial hyperlipidemia is also improved by dietary lipids, which generally show lower PPAR ␣ activation than synthesized PPAR ␣ agonists ( 34,35 ). Previous studies have indicated that DHA increases mRNA expression levels of FA oxidation-related genes in intestinal epithelial cells ( 36,37 ) and that PUFAs including DHA enhance FA oxidation in hepatocytes ( 38 ). The present others have recently demonstrated that PPAR ␣ agonists improve postprandial hyperlipidemia through increasing FA oxidation in intestinal epithelial cells ( 15,16 ).…”
Section: Dha-rich Oil Attenuated Postprandial Tg Levels By Reducing Tmentioning
confidence: 99%
“…Transcription factors play an important role in IBD (Heimerl et al, 2006;Sanderson et al, 2008), for example NFB in regulating production and activation of pro-inflammatory cytokines (Mitsuyama et al, 2001). Nuclear receptors, a family of ligand-activated transcription factors, are most relevant in mediating the effect of nutrients and their metabolites on gene transcription (De Vogel-van den Bosch, 2008) and can directly or indirectly regulate genes of lipid metabolism and inflammatory signalling (Schmitz and Ecker, 2008). Nuclear receptors that regulate PUFA-induced gene expression include peroxisome proliferatoractivated receptors (PPAR, NR1C), liver X receptor (LXR, NR1H), retinoid X receptor (RXR, NR2B), hepatocyte nuclear factor 4 (HNF4), farnesoid X receptor (FXR, NR1H) and pregnane X receptor (PXR, NR1I) (Heimerl et al, 2006;Salter and Tarling, 2007;Sanderson et al, 2008).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…for particular diseases or physiological states) of organisms with a sequenced genome, allowing investigators to establish gene networks and identify new genes involved in the investigated trait. Gene expression profiling, or transcriptomics, is widely used in both biomedical (Subramanian et al, 2005) and nutrition (Müller and Kersten, 2003) research to characterize molecular-pathway and network data in a variety of tissues in laboratory animals (Langmann et al, 2004;Rivera et al, 2006;Dommels et al, 2007) and in response to dietary treatments to predict a phenotypic outcome (De Vogel-van den Bosch et al, 2008;Nones et al, 2008;Sanderson et al, 2008).…”
Section: A Molecular Approach To Study Polyunsaturated Fatty Acid-regmentioning
confidence: 99%